Behavioral determinants related to the incidence of diarrhea among students in Samarinda City - Rahayu, Eka Putri; Chifdillah, Nino Adib; Tonapa, Emelia (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to investigate behavioral determinants associated with the incidence of diarrhea among elementary school students in Samarinda City. Methods: This research employed a Cross-Sectional design. There was a population of 126 students in the 5th and 6th grades. The number of samples was calculated using the Slovin formula, resulting in 78 respondents selected through simple random sampling. Results: Behavioral determinants of diarrhea consist of hand washing with soap, toilet use, nail cleanliness, snack habits, and peer influence. Statistical analysis revealed significant findings. Snack habits and peer influence were found to have no significant effect on the incidence of diarrhea (ρ-value = 0.063 and ρ-value = 0.083). However, factors such as hand washing with soap (p-value = 0.023), toilet use (p-value = 0.000), and nail cleanliness (p-value = 0.002) had significant effects on the incidence of diarrhea. The use of toilets received an OR value of 35, indicating that respondents with toilet hygiene behaviors have a 35 times higher risk of experiencing diarrhea. Conclusion: Toilet use is the strongest predictor (35 times higher risk when proper toilet hygiene is not practiced).